Mechanism of triphenylmethane Cresol Red degradation by Trichoderma harzianum M06 - Nurafifah Mohd Nor; Tony Hadibarata; Meor Mohd Fikri Ahmad Zubir; Zainab Mat Lazim; Liyana Amalina Adnan; Mohamad Ali Fulazzaky (Springer, 2024)
Bioprocess and Biosystems Engineering volume 38, pages2167–2175 (2015)